The Efficacy of High Flow Nasal Cannula (HFNC) in Chronic Obstructive Pulmonary Disease (COPD): a Case Report - Prasetya, Raka Jati; Sitio, Nurita Dian Kestriani Saragi (CoinReads Media Prima, 2023)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a heterogeneous lung condition characterized by chronic respiratory symptoms due to abnormalities of the airways and/or alveoli (that cause persistent, often progressive, airflow obstruction. The main environmental exposures leading to COPD are tobacco smoking and the inhalation of toxic particles and gases from household and outdoor air pollution. COPD could lead to worse outcomes from COVID-19. Oxygen therapy is the main treatment method for patients with COPD and hypoxemia. Compared with NIV, HFNC can significantly reduce the incidence of pressure injuries such as facial and nasal bridge rupture. And also HFNC could be a valuable and feasible treatment option for patients with COVID-19 pneumonia, with remarkable clinical advantages. Method: This was a retrospective case report, after analysis of patient clinical data. The patient provided written informed consent to publish their case details and any accompanying images. Results: A 63-year-old man was presented with a complaint of shortness of breath that had been felt for two days before entering the hospital. The first day of treatment, the patient complained of increasing severe shortness of breath accompanied by fever. Later on, the patient was diagnosed with an acute exacerbation of COPD accompanied by COVID-19. During 4 days of hospitalization, the patient was admitted to the ICU because of worsening breathing and was given oxygen therapy with HFNC and other drugs for 8 days. Patient showed improvement and was then discharged after seven days of hospitalization. Conclusion: HFNC can be an alternative therapy in COPD therapy with COVID 19, because it has good tolerance and physiological effects